Mountain time : a novel - Doig, Ivan (Scribner, 1999)
Set in Seattle, Montana, and Alaska, "Mountain Time" tells a story about a generation that has reached its time of reckoning. Vividly described, Doig's story brings to light the necessity of settling family issues in order to move on to more satisfying relationships.